2014
DOI: 10.3109/02713683.2014.883412
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 Contributes to the Host Response toKlebsiellaIntraocular Infection

Abstract: Purpose/Aim Klebsiella pneumoniae causes a blinding infection called endogenous endophthalmitis. The role of innate immune recognition of K. pneumoniae in the eye during infection is not known. We hypothesized that intraocular recognition of K. pneumoniae was mediated by TLR4 and may be dependent on MagA-regulated hypermucoviscosity. Materials and Methods Experimental endophthalmitis was induced in C57BL/6J or TLR4−/− mice by intravitreal injection of 100 CFU of wild type or ΔmagA K. pneumoniae. Infection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…We recently reported that the absence of TLR4 resulted in a delayed inflammatory response in experimental Klebsiella pneumoniae endophthalmitis (38). Tullos et al also proposed that TLR2 and TLR4 modulated the immune response in a Streptococcus pneumoniae keratitis model, with TLR2 aiding in bacterial clearance and the absence of TLR4 contributing to reduced disease pathogenesis (53).…”
Section: Fig 9 Proinflammatory Mediator Expression In Tlr4mentioning
confidence: 98%
See 1 more Smart Citation
“…We recently reported that the absence of TLR4 resulted in a delayed inflammatory response in experimental Klebsiella pneumoniae endophthalmitis (38). Tullos et al also proposed that TLR2 and TLR4 modulated the immune response in a Streptococcus pneumoniae keratitis model, with TLR2 aiding in bacterial clearance and the absence of TLR4 contributing to reduced disease pathogenesis (53).…”
Section: Fig 9 Proinflammatory Mediator Expression In Tlr4mentioning
confidence: 98%
“…Analysis of phagocytosis and killing activity was performed with freshly isolated neutrophils from C57BL/6J and TLR4 Ϫ/Ϫ mice (37,38). B. cereus strain ATCC 14579 and neutrophils were incubated separately in PBS containing 10% heat-inactivated C57BL/6J mouse serum at 37°C (Valley Biomedical Products, Winchester, VA).…”
Section: Phagocytosis and Killing Neutrophils From C57bl/6j And Tlr4mentioning
confidence: 99%
“…In clinical settings, most bacterial endophthalmitis arises due to postsurgical complications (e.g., cataract surgery), where pathogens from the ocular surface gain access to the eye and cause ocular tissue damage [28,29]. To mimic this situation, studies from our [7,26,30] and other laboratories [31,32] have developed murine models where bacteria are directly inoculated in the vitreous cavity. Previous studies have demonstrated that S. aureus caused endophthalmitis in mice when eyes were inoculated with 5000 or less CFUs [7,10,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, deficiencies in Toll/IL-1 receptor domain-containing adapter-inducing interferon β (TRIF, the intracellular adaptor molecule for TLR4) and in TLR4 itself also resulted in significantly less intraocular inflammation during experimental B. cereus endophthalmitis, suggesting that MyD88-independent pathways were involved in the intraocular response to B. cereus and that B. cereus may harbor ligands for TLR4 which instigate intraocular inflammation (Parkunan et al, 2015). The importance of TLR4 in experimental K. pneumoniae endophthalmitis was demonstrated using TLR4-deficient mice (Hunt et al, 2014). The data on the course of infection in the K. pneumoniae endophthalmitis mouse model (Wiskur et al, 2008a) were cited by Ishii et al as providing guidance in the successful treatment of a patient with K. pneumoniae endophthalmitis (Ishii et al, 2011), emphasizing the clinical value of these experimental models.…”
Section: Experimental Models: Therapeutics and Virulencementioning
confidence: 99%
“…Polymorphonuclear neutrophils (PMN) have been identified as the earliest cell type to invade the posterior segment and retina during endophthalmitis caused by a number of species (Booth et al, 1995; Hunt et al, 2014; Jett et al, 1992; Ramadan et al, 2006; Sanders et al, 2010; Talreja et al, 2014). PMN infiltration coincided with permeability of the blood-ocular barrier which, in mice, occurred as early as four hours post- Bacillus infection (Moyer et al, 2009).…”
Section: Experimental Models: Therapeutics and Virulencementioning
confidence: 99%